2023
DOI: 10.1021/acs.jpclett.3c02222
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Potential of [B12X11]2– (X = F, Cl, Br, I, CN) Dianions

Mehmet Emin Kilic,
Puru Jena

Abstract: Dodecaborate anions ([B12H12]2–) and their derivatives where hydrogen atoms are replaced by halogen, pseudohalogen, or superhalogen moieties belong to a class of very stable species, even in the gas phase. Their stability is attributed to Wade’s electron counting rule that requires n + 1 pairs of skeletal electrons, n being the number of boron atoms. Consequently, [B12 X 11]2– (X = H, F, Cl, Br, I, CN) dianions that carry one more electron than needed to satisfy Wade’s rule should not be stable, assuming tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The angular distortion is found to be more for the SrO-terminated surface except for the case of (Ni, 2F) doping. These observations are favorable for weakening the CO 2 molecule, thereby activating it, as reported by Kilic and Jena …”
Section: Resultssupporting
confidence: 67%
“…The angular distortion is found to be more for the SrO-terminated surface except for the case of (Ni, 2F) doping. These observations are favorable for weakening the CO 2 molecule, thereby activating it, as reported by Kilic and Jena …”
Section: Resultssupporting
confidence: 67%
“…The geometries and total energies of [B 12 X 12 ], [B 12 X 11 ] n − , and [B 12 X 11 ] n − ( n = 0, 1, 2; X = H, F, CN) clusters interacting with small molecules, Y = H 2 , O 2 , CO, and NH 3 , are calculated using density functional theory (DFT) and the B3LYP exchange-correlation functional . We used the Gaussian 16 code with the 6-31+G­(d,p) basis set for all atoms as this choice has led to good agreement between theory and experiment . All the structures are fully optimized without any symmetry constraint.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent article, we showed that if one of the ligands X from [B 12 X 12 ] 2– (X = F, CN) could be removed in neutral form, the resulting cluster, [B 12 X 11 ] 2– , can remain stable against the detachment of the second electron. This is consistent with an earlier experimental observation of [B 12 Br 11 ] 2– .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron-rich carbides (e.g., B 4 C and B 13 C 2 ) are exemplary cases among boron-rich compounds that exhibit unique properties of high hardness (30–50 GPa) and low density (∼2.5·gcm –3 ), with applications in body armor, cutting tools, and neutron radiation absorbents. However, owing to low fracture toughness (3–4 MPa·m 1/2 ), B 4 C exhibits brittle failure under high pressure while forming amorphous shear bands. To design and synthesize lightweight materials with excellent mechanical properties, various boron-rich compounds have been extensively explored, e.g., B 6 O, B 13 C 2 , and B 13 CN. In boron-rich compounds, a B 12 icosahedron serves as the skeleton unit in which two-center two-electron (2c-2e) and three-center two-electron (3c-2e) bonding configurations coexist and exhibits unique bonding characteristics because of its electron-deficient nature. The mechanical properties of boron-rich compounds are highly sensitive to their electron-filling states because of the electron-deficient icosahedrons and electron-compensating atomic chains. Thus, understanding their mechanical properties under various electron-filling states is crucial.…”
mentioning
confidence: 99%